Ensuring Learning Independence through Self- Awareness in Primary School Students - Mahmudova, Nodira (International Journal of Development and Public Policy, 2022)
The article not only describes the concepts of self-awareness, cognitive activity, creative orientation, initiative, ability to set goals, the ability to plan their work for primary school students., focuses on aspects of elementary school students’ physical and mental abilities, behaviors and their motives, being around, and self-awareness.